Praktik Manajemen Strategis Terhadap Kinerja Organisasi - Hariri Hariri; Aspuri Aspuri; Dian Wirtadipura (Amal Insani Foundation, 2023)
Today, performance management ensures and protects organizational effectiveness and efficiency in many countries. Although performance measurement is expressed as the effectiveness of strategy and efficiency of activities, more is needed to ensure overall organizational performance, and the concept of impact must be integrated with all other elements for organizational performance. Changes in the structure and functioning of organizations in competitive conditions, the increasing importance of decisions made by top management, and their contribution to the organization make it important to manage performance effectively.